Shift in size of bumblebee queens over the last century. (29th November 2019) - Gérard, Maxence; Martinet, Baptiste; Maebe, Kevin; Marshall, Leon; Smagghe, Guy; Vereecken, Nicolas J.; Vray, Sarah; Rasmont, Pierre; Michez, Denis
Abstract: Species can respond differently when facing environmental changes, such as by shifting their geographical ranges or through plastic or adaptive modifications to new environmental conditions. Phenotypic modifications related to environmental factors have been mainly explored along latitudinal gradients, but they are relatively understudied through time despite their importance for key ecological interactions. Here we hypothesize that the average bumblebee queen body size has changed in Belgium during the last century. Based on historical and contemporary databases, we first tested if queen body sizes changed during the last century at the intraspecific level among four common bumblebee species and if it could be linked to global warming and/or habitat fragmentation as well as by the replacement by individuals from new populations. Then, we assessed body size changes at the community level, among 22 species, taking into account species population trends (i.e. increasing, stable or decreasing relative abundance). Our results show that the average queen body size of all four bumblebee species increased over the last century. This size increase was significantly correlated to global warming and habitat fragmentation, but not explained by changes in the population genetic structure (i.e. colonization). At the community level, species with stable or increasing relative abundance tend to be larger than declining species. Contrary to theoretical expectations from Bergmann's rule (i.e. increasing body size in colder climates), temperature does not seem to be the main driver of bumblebee body size during the last century as we observed the opposite body size trend. However, agricultural intensification and habitat fragmentation could be alternative mechanisms that shape body size clines. This study stresses the importance of considering alternative global change factors when assessing body size change. Abstract : We show that queens of four common bumblebee species have increased in size over the last century in Belgium. These results are contrary to the idea that warmer temperatures should lead to smaller populations, and indicates that landscape fragmentation and agricultural intensification in Belgium are likely to have driven this shift towards larger queens. We also show that out of 22 species, larger species tend to be doing better and are more likely to show a stable or increasing trend. This provides evidence that larger bumblebee species may be less susceptible to the impacts of global change. See also the Commentary on this article by Jauker, https://doi.org/10.1111/gcb.14967